Pengaruh Pemberian Terapi Labusiam Untuk Menurunkan Tekanan Darah Pada Pasien Hipertensi - Intan Safitri; Solehudin Solehudin; Bambang Suryadi (STIKes Ibnu Sina Ajibarang, 2023)
. Hypertension is a problem that needs attention because it does not have extraordinary manifestations. One procedure that can be used to overcome the problem of hypertension is non-pharmacological vegetables and other natural ingredients. The aim of this study was to determine the effect of giving labusiam therapy in reducing blood pressure in hypertensive patients. Method: This research is quantitative using a pre-experimental design method with a one group pre-post test design. The number of samples used was 15 respondents, the sampling technique used an accidental sampling approach. The statistical test in this study used the Wilcoxon Test. This research was conducted in Bogor, West Java. Results: It is known that the average MAP value before the intervention was 117 mmHg and after the intervention it decreased to 106 mmHg. Based on the Wilcoxon test, it is known that there is a difference in the average MAP value before and after the intervention (0.001 < 0.005). Conclusion: givinbusiam food has a significant positive effect on reducing blood pressure in hypertensive